2016
DOI: 10.1016/j.jpain.2015.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Role of Kv4.3 in Vibration-Induced Muscle Pain in the Rat

Abstract: We hypothesized that changes in the expression of Kv4.3 contribute to the mechanical hyperalgesia induced by vibration injury, a rodent model for hand-arm vibration syndrome in humans. Here we show that the exposure of the gastrocnemius muscle to vibration injury induces muscle hyperalgesia that is accompanied by a significant down-regulation of Kv4.3 in affected sensory nerve fibers in dorsal root ganglia (DRG). We additionally demonstrate that the intrathecal administration of antisense oligonucleotides for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…Nevertheless, in our present study, HpTx3 used in several pain models showed potent analgesic activity, suggesting that the analgesic effect of HpTx3 overwhelmed the hyperalgesia it caused. This result may be explained at least partially by the fact that in the pain models the level of K v 4 channels is usually decreased [56,61,64,65]. Till now, only one model showed that the expression of K v 4 channels was increased following injury [58].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in our present study, HpTx3 used in several pain models showed potent analgesic activity, suggesting that the analgesic effect of HpTx3 overwhelmed the hyperalgesia it caused. This result may be explained at least partially by the fact that in the pain models the level of K v 4 channels is usually decreased [56,61,64,65]. Till now, only one model showed that the expression of K v 4 channels was increased following injury [58].…”
Section: Discussionmentioning
confidence: 99%
“…injection of antisense (AS) oligodeoxynucleotides (ODN) directed against IL-10R1 mRNA. This approach has been shown to produce a reversible inhibition of the expression of several proteins involved in pain processing in DRG neurons (for a review see [49]) and to modulate a number of behavioral nociceptive responses, including mechanical hyperalgesia in skeletal muscle [24,13,17]. The AS ODN sequence, 5′-TTG TCC CGT AGA TGA AGC CGT TGC-3′, was directed against a unique sequence in rat IL-10R1 mRNA.…”
Section: Methodsmentioning
confidence: 99%
“…Changes in IL-10R1 expression in lumbar DRGs were evaluated by Western blot analysis as previously described [13]. Briefly, rats were euthanized by exsanguination, while under deep isoflurane anesthesia, 24 h after the last i.t.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent studies showed that Kv4.3 DRG immunoreactivity is reduced by 40% following nerve ligation (Chien et al, 2007 ). Vibration induced injury decreases Kv4.3 mRNA in the nerves innervating the affected side (Conner et al, 2016 ). In streptozotocin (STZ)-induced diabetic neuropathy, there are robust decreases in A-type Kv currents and Kv4 expression in putative nociceptors after disease onset (Cao et al, 2010 ; Grabauskas et al, 2011 ; Sun et al, 2011 ).…”
Section: Function and Dysfunction Of A-type Kv Channel Subtypes In Drmentioning
confidence: 99%
“…Three days of intrathecal administration of Kv4.3 antisense oligonucleotides induces mechanical allodynia but not thermal hyperalgesia (Chien et al, 2007 ). A separate group also injected Kv4.3 channel antisense oligonucleotides and have shown increased sensitization to vibration (Conner et al, 2016 ). In a bone cancer model of chronic pain, injection of Kv4.3 siRNA in the lumbar spinal cord prohibits the ability of diclofenac to reverse the mechanical allodynia phenotype with no effect on thermal hyperalgesia (Duan et al, 2012 ).…”
Section: Function and Dysfunction Of A-type Kv Channel Subtypes In Drmentioning
confidence: 99%